At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To address the problem, we start by understanding the given statement [tex]\(\sim q \rightarrow \sim r\)[/tex]. Let's break down its logical components and then derive the converse, inverse, and contrapositive.
### Given Statement
[tex]\[ \sim q \rightarrow \sim r \][/tex]
This reads as "if not [tex]\( q \)[/tex], then not [tex]\( r \)[/tex]."
### Converse
The converse of a conditional statement [tex]\(p \rightarrow q\)[/tex] is derived by swapping the hypothesis and conclusion. So, for the given statement [tex]\(\sim q \rightarrow \sim r\)[/tex]:
- Original hypothesis: [tex]\(\sim q\)[/tex]
- Original conclusion: [tex]\(\sim r\)[/tex]
Switch these to get the converse:
[tex]\[ \sim r \rightarrow \sim q \][/tex]
### Answer Choices for the Converse
Given the following options:
A. [tex]\(q \vee \sim r\)[/tex]
B. [tex]\(r \rightarrow q\)[/tex]
C. [tex]\(q \rightarrow r\)[/tex]
D. [tex]\(\sim r \rightarrow \sim q\)[/tex]
The correct choice that matches the derived converse ([tex]\(\sim r \rightarrow \sim q\)[/tex]) is:
[tex]\[ \text{D. } \sim r \rightarrow \sim q \][/tex]
### Inverse
The inverse of a conditional statement [tex]\(p \rightarrow q\)[/tex] is derived by negating both the hypothesis and the conclusion:
- Original statement: [tex]\(\sim q \rightarrow \sim r\)[/tex]
- Negate the hypothesis: [tex]\(q\)[/tex]
- Negate the conclusion: [tex]\(r\)[/tex]
Thus, the inverse is:
[tex]\[ q \rightarrow r \][/tex]
### Contrapositive
The contrapositive of a conditional statement [tex]\(p \rightarrow q\)[/tex] is derived by swapping the hypothesis and conclusion of the inverse.
- Original statement: [tex]\(\sim q \rightarrow \sim r\)[/tex]
- Inverse: [tex]\(q \rightarrow r\)[/tex]
- Swap the hypothesis and conclusion of the inverse:
[tex]\[ \sim r \rightarrow \sim q \][/tex]
Interestingly, the contrapositive and the converse for the given statement are identical in form.
### Summary
- Converse: [tex]\(\sim r \rightarrow \sim q\)[/tex] (Answer: D)
- Inverse: [tex]\(q \rightarrow r\)[/tex]
- Contrapositive: [tex]\(\sim r \rightarrow \sim q\)[/tex]
Therefore, the correct answer to the question "The converse of the given statement is which of the following?" is:
[tex]\[ \text{D. } \sim r \rightarrow \sim q \][/tex]
### Given Statement
[tex]\[ \sim q \rightarrow \sim r \][/tex]
This reads as "if not [tex]\( q \)[/tex], then not [tex]\( r \)[/tex]."
### Converse
The converse of a conditional statement [tex]\(p \rightarrow q\)[/tex] is derived by swapping the hypothesis and conclusion. So, for the given statement [tex]\(\sim q \rightarrow \sim r\)[/tex]:
- Original hypothesis: [tex]\(\sim q\)[/tex]
- Original conclusion: [tex]\(\sim r\)[/tex]
Switch these to get the converse:
[tex]\[ \sim r \rightarrow \sim q \][/tex]
### Answer Choices for the Converse
Given the following options:
A. [tex]\(q \vee \sim r\)[/tex]
B. [tex]\(r \rightarrow q\)[/tex]
C. [tex]\(q \rightarrow r\)[/tex]
D. [tex]\(\sim r \rightarrow \sim q\)[/tex]
The correct choice that matches the derived converse ([tex]\(\sim r \rightarrow \sim q\)[/tex]) is:
[tex]\[ \text{D. } \sim r \rightarrow \sim q \][/tex]
### Inverse
The inverse of a conditional statement [tex]\(p \rightarrow q\)[/tex] is derived by negating both the hypothesis and the conclusion:
- Original statement: [tex]\(\sim q \rightarrow \sim r\)[/tex]
- Negate the hypothesis: [tex]\(q\)[/tex]
- Negate the conclusion: [tex]\(r\)[/tex]
Thus, the inverse is:
[tex]\[ q \rightarrow r \][/tex]
### Contrapositive
The contrapositive of a conditional statement [tex]\(p \rightarrow q\)[/tex] is derived by swapping the hypothesis and conclusion of the inverse.
- Original statement: [tex]\(\sim q \rightarrow \sim r\)[/tex]
- Inverse: [tex]\(q \rightarrow r\)[/tex]
- Swap the hypothesis and conclusion of the inverse:
[tex]\[ \sim r \rightarrow \sim q \][/tex]
Interestingly, the contrapositive and the converse for the given statement are identical in form.
### Summary
- Converse: [tex]\(\sim r \rightarrow \sim q\)[/tex] (Answer: D)
- Inverse: [tex]\(q \rightarrow r\)[/tex]
- Contrapositive: [tex]\(\sim r \rightarrow \sim q\)[/tex]
Therefore, the correct answer to the question "The converse of the given statement is which of the following?" is:
[tex]\[ \text{D. } \sim r \rightarrow \sim q \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.